2015
DOI: 10.1037/a0038088
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on age differences in risky decision making: Adolescents versus children and adults.

Abstract: Despite evident heightened adolescent risk-taking in real-life situations, not all experimental studies demonstrate that adolescents take more risks than children and adults on risky decision-making tasks. In the current 4 independent meta-analyses, neurodevelopmental imbalance models and fuzzy trace theory were used as conceptual frameworks to examine whether adolescents engage in more risk-taking than children and adults and whether early adolescents take more risks than children and mid-late adolescents on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
343
3
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(386 citation statements)
references
References 141 publications
(347 reference statements)
18
343
3
13
Order By: Relevance
“…Furthermore, despite previous evidence that the effects of emotion on risk taking are greater in adolescence than in adulthood (Defoe et al, 2015), the impact of missed opportunities, an implicit measure of regret, was greatest in a group of adults. In other words, the effects of regret responsivity on risk taking continue to increase into adulthood.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, despite previous evidence that the effects of emotion on risk taking are greater in adolescence than in adulthood (Defoe et al, 2015), the impact of missed opportunities, an implicit measure of regret, was greatest in a group of adults. In other words, the effects of regret responsivity on risk taking continue to increase into adulthood.…”
Section: Discussioncontrasting
confidence: 62%
“…Much developmental work on risky decision-making has focussed on adolescents (see Boyer, 2006;Hartley & Somerville, 2015), who are often thought to be more risk seeking than younger children or adults (see Steinberg, 2007). Adolescents are particularly likely to take risks in so-called "hot" decision-making tasks where immediate outcome feedback is provided, consistent with suggestions that affect plays a larger role in adolescent than adult decision-making (Defoe, Dubas, Figner, & Van Aken, 2015;Steinberg, 2007). If adolescent decisionmaking is particularly susceptible to emotional influences, one obvious hypothesis is that regret arising out of information about missed opportunities will have a greater impact on decision-making in adolescents than in children or in adults.…”
Section: Brief Articlementioning
confidence: 94%
“…Finally, in consideration of reported age and gender differences in impulsivity (Cross et al, 2011;Lauriola et al, 2014), risk-taking (Byrnes et al, 1999;Defoe et al, 2015), and alcohol use behaviours (Erol & Karpyak, 2015), the first stage of each model included age and gender as controls. Inconsistent with previous research (Livingston & Room, 2009), gender did not predict any alcohol consumption behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Gender and age were entered into the regression models first in order to control for age and gender-related differences in risk-taking (Byrnes, Miller, & Schafer, 1999;Defoe, Dubas, Figner, & van Aken, 2015), impulsivity (Cross, Copping, & Campbell, 2011;Lauriola, Panno, Levin, & Lejuez, 2014), and alcohol use (Erol & Karpyak, 2015).…”
Section: Analytic Strategymentioning
confidence: 99%
“…It may be that, apart from age, other individual and social (such as peer pressure) or contextual factors play a prominent role in behavioral addictions such as gambling. Recently, Defoe et al (2015) made reference to risk-taking opportunities and suggested a hybrid developmental neuroecological model of risk-taking that includes a risk opportunity component.…”
Section: Insert Table 2 About Here Discussionmentioning
confidence: 99%